Psychological factors’ influence on consumers’ propensity to indebtedness applying the behavioural economic theory - Selvaraja, Monica; Abdullah, Amalina (Academic Star, 2020)
The purpose of this paper is to develop a conceptual model to examine the multidimensionality of psychological factors and its impact on the propensity to indebtedness. The background of psychological factor and the theory of behavioural economic serve as a starting-point to develop the conceptual model. From the extensive literature review, four dimensions of psychological factor were identified to construct the model. The model based on the psychological factor with respect to the propensity to indebtedness provides a basis for assessing the level of debt and the role of psychological factors under which the use of various aspects of psychological factors should be the further emphasis and enhanced. This finding suggests that psychological factors are not a panacea that can be enhanced but must be imparted gradually through awareness with a clear sense of impact to the propensity to indebtedness. Given that propensity to indebtedness are often detrimental to consumers’ insolvency, it is appropriate for interested parties to invest time and effort to diagnose the influence psychological factors have on the propensity to indebtedness, hence, this model will prove valuable. This conceptual model provides an insightful foundation for the analysis of multidimensionality of psychological factors on the propensity to indebtedness.